"A Descoberta" - Joana Maria da Rocha Pacheco (2020)
The aim of this report is to portray and ponder critically and in a substantiated manner about the teaching-learning process during the Professional Physical Education Teacher Training. Practical situations that took place throughout the school year, which contributed to our professional and personal growth, will be addressed, ranging from traineeship experiences, obstacles faced, problems that have arisen and ultimately overcome. My Professional Teacher Training took place at a cooperating school from the Agrupamento de Escolas de Valongo, the Valongo Secondary School, which is part of the group of schools with a protocol with FADEUP. This report is organized in 6 chapters: 1 - Introduction, where I give a general description of the Professional Teacher Training; 2 - Personal Discovery, where I portray the background that led me into choosing teaching and PE, as well as the expectations and impact it had in the Professional Training; 3 - Institutional Discovery, where I report my experience as a teacher in training and everything that it involves; 4 - Operational Discovery, which is divided into three areas. Area 1 - Organization and Management of Teaching and Learning, which reflects the drafting, planning, execution and performance evaluation. Area 2 - Engagement and relationship with the School Community depicting the activities that took place during the teacher training. Area 3 - Professional Development, describes the important activities and efforts during the development of professional competence and research; 5 - Final Considerations, reflecting the entire trajectory of the Professional Training and 6 - Bibliographic References used.